Thyroid hormone metabolism in poultry - Darras, V.M; Geyten, S. van der; Kuehn, E.R. (Katholieke Univ. Leuven (Belgium). Faculteit Landbouwkundige en Toegepaste Biologische Wetenschappen) (Biotechnologie, agronomie, société et environnement, 2000)
Thyroid hormone (TH) receptors preferentially bind 3.5,3'-triiodothyronine (T3). Therefore the metabolism of thyroxine (T4) secreted by the thyroid gland in peripheral tissues, resulting in the production and degradation of receptor-active T3, plays a major role in thyroid function. The most important metabolic pathway for THs is deiodination. Another important pathway is sulfation, which is a reversible pathway that has been shown to interact with TH deiodination efficiency. The enzymes catalysing TH deiodination consist of three types. Type 1 deiodinase (D1) catalyses both outer ring (ORD) and inner ring deiodinalion (IRD). Type II deiodinase (D2) only catalyses ORD while type III (D3) only catalyses IRD. The three chicken deiodinase cDNAs have been cloned recently. These enzymes all belong to the family of selenoproteins. Ontogenetic studies show that the availability of deiodinases is regulated in a tissue specific and developmental stage dependent way. Characteristic for the chicken is the presence of very high levels off, inactivating D3 enzyme in the embryonic liver. Hepatic D3 is subject to acute regulation in a number of situations. Both growth hormone and glucocorticoid injection rapidly decrease hepatic D3 levels, hereby increasing plasma T3 without affecting hepatic D1 levels. The inhibition of D3 seems to be regulated mainly at the level of D3 gene transcription. The effect of growth hormone on D3 expression persists throughout life, while glucocorticoids start to inhibit hepatic D1 expression in posthatch chickens. Food restriction in growing chickens increases hepatic D3 levels. This contributes to the decrease in plasma T3 necessary to reduce energy loss. Refeeding restores hepatic D3 and plasma T3 to control levels within a few hours. It can be concluded that the tissue and time dependent regulation of the balance between TH activating and inactivating enzymes plays an essential role in the control of local T3 availability and hence in TH activity.